Performance of SARS-CoV-2 rapid antigen test compared with real-time RT-PCR in asymptomatic individuals. (June 2021) - Peña, Mónica; Ampuero, Manuel; Garcés, Carlos; Gaggero, Aldo; García, Patricia; Velasquez, María Soledad; Luza, Ricardo; Alvarez, Pía; Paredes, Fabio; Acevedo, Johanna; Farfán, Mauricio J.; Solari, Sandra; et al.
Highlights: This review assessed the performance of the SD Biosensor antigen test compared to RT-PCR. It reported a sensibility of 69.86% and specificity of 99.61%. The SD Biosensor antigen test enabled rapid identification of asymptomatic individuals. Abstract: Screening, testing and contact tracing plays a pivotal role in control of the COVID-19 pandemic. To enable this it is necessary to increase the testing capacity. This study compared a SARS-CoV-2 rapid antigen test (RAT) and RT-PCR in 842 asymptomatic individuals from Tarapacá, Chile. A sensitivity of 69.86%, specificity of 99.61%, PPV of 94.44% and NPP of 97.22% with Ct values (Ct > 27) that were significantly higher among individuals with false-negative RAT were reported. These results support the fact that RAT might have a significant impact on the identification of asymptomatic carriers in areas that lack suitable laboratories to perform SARS-CoV-2 real-time RT-PCR diagnostics, or the results take more than 24–48 h, as well as zones with high traffic of individuals such as border/customs, airports, interregional bus, train stations or in any mass testing campaign requiring rapid results.